2018
DOI: 10.1108/ijlma-01-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of corporate governance on the stock return volatility

Abstract: Purpose The purpose of this study is to investigate the relationship between the stock return volatility, the outside and the independent directors. Design/methodology/approach The volatility, as the dependent variable in the model, is measured by the standard deviation of annual stock returns. Concerning the independent variable is as follows: The chief executive officer (CEO) is a dummy variable denoting whether or not the chairman of the board holds the position of CEO. The INDD, which represents the inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 74 publications
2
10
0
1
Order By: Relevance
“…A company with a high debt to equity ratio is proven to be able to provide greater benefits for shareholders, if the company is able to use its debt effectively for the company's business development. Research by [33] also found the same results that there was a positive and significant influence between the solvency ratio on stock return. In addition, [34] also stated that there is a positive and significant influence between the solvency ratio on stock return.…”
Section: Growth Ratesupporting
confidence: 55%
“…A company with a high debt to equity ratio is proven to be able to provide greater benefits for shareholders, if the company is able to use its debt effectively for the company's business development. Research by [33] also found the same results that there was a positive and significant influence between the solvency ratio on stock return. In addition, [34] also stated that there is a positive and significant influence between the solvency ratio on stock return.…”
Section: Growth Ratesupporting
confidence: 55%
“…Taking the punctual results, the coefficients estimated from the models, we found that the IGC index presents the volatility more reactive and less persistent than the TRAD index, opposing the idea that the stocks with good governance practices are better protected from the short-term movements (Rogers and Securato, 2009;Giroud and Mueller, 2011;Huang et al, 2011;An and Zhang, 2013;Chen et al, 2013;Kim et al, 2014;Asker et al, 2015;Vo, 2015;Aloui and Jarboui, 2018). However, in the long-run, and considering the error measures, they are following the same pattern.…”
Section: Notesmentioning
confidence: 70%
“…Therefore, poor corporate governance increases stock price volatility due to the reduction of monitory mechanism and investors' confidence in firms. A stable stock volatility is important when the investor operates in an uncertain environment, especially those who are going through some crisis as Brazil in the current decade (Aloui and Jarboui, 2018). Other factors also influence the stock volatility as ownership for foreign corporations and individuals (Chen et al, 2013) and these foreign investors have a stabilizing role in emerging stock market (Vo, 2015).…”
Section: Corporate Governance and Volatility Term Structurementioning
confidence: 99%
“…The elements of corporate governance use institutional ownership, independent commissioners, dual CEO positions and CEO tenure. [11] in research on the effect of corporate governance on fluctuations in stock returns during the financial crisis, it is stated that there is a relationship between independent commissioners and outside directors on fluctuations in stock returns. [12] states that there is a positive and significant relationship between corporate governance and stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%